Body and voice : somatic re-education - Gilman, Marina (Plural Publishing Inc., 2014)
This book contains a series of lessons designed to train singing teachers, coaches, and voice therapists to recognize in their students the patterns of use and posture that interfere with respiration, phonation, and/or resonance. In addition, it provides tools for the teacher to guide the student to a level of self-awareness of habituated patterns along with strategies to implement change from the inside out.